THE VIOLENCE - AN ELEMENT OF VIOLENT CRIMINALITY OR A WAY OF MODERN LIVING - Velkova, Tatjana; Hadjijevska, Sofka (European Scientific Journal, ESJ, 2014)
The use of force in any form, against another person, against someone else’s or their own personal property is the mutual element of the criminological classification of the violent crime as one of the severest types of incriminated human behaviours. However, modern lifestyle and the dynamics of people and events suggest constant embedding of the violence and its emergent types in everyday life and in all spheres of the individual’s life in society. Hence the subject of this paper is violence and the forms in which it can occur, i.e. its importance as an element of violent crime on one hand, and its importance as a way of acting and living, on the other. This leads to the assumption that violence due to the modern lifestyle is no longer just an element of violent crime, but it is becoming more and more widely spread lifestyle. Therefore, the aim of this paper is to point out and emphasize that collective consciousness should not and must not subjugate to the belief that it is normal to tolerate violence and to accept it as inevitable segment of modern living. In this sense, in order to realise the goal of the paper and to validate the assumption that has been set, it is necessary to analyse the current situation regarding the use of violence, not only when committing criminal offenses, but also in everyday life and community functioning.